Situation and Trends of Educational Management in Thailand to Meet the Country Development Needs 2019 - Chatakan, Werayut; Chairueng, Nopparat; Assawasowan, Jutiporn (International Journal of Psychosocial Rehabilitation, 2020)
The main objectives of the study are the current situations and trends of Thai education management to link the country needed in 2019 1) study current situations and trends of education management according to Education Development Plan (2017-2036) and National Strategy (2018-2037) and 2) make a policy suggestion through education strategy (2017-2037) and education reforming. This research is a future or foresight study with three steps through the mixed method with four stages: bibliometric, gap analysis, priority needs index (PIN), and trend analysis. There are three stages in this research. 1) Analysis of the relation, gaps, and goals of the national strategic plan and Thailand's 20 - Year National Education 2) Analysis of the Thai educational situations in 2019 according to the research framework. 3) Analysis of the policy and also the suggestions to develop Thai education. The research findings were as follows:1. The results of the analysis of relation and gap between goals of National Strategy (2018-2037) and Education Development Plan (2017-2036) found links between target goals of National Strategy (2018-2037) indicators and Education Development Plan (2017-2036) in strategy, goal, and indicators relate to each other without weak points.2. The results of the analysis of Thai education situations according to goals and indicators of the Education Development Plan (2017-2036). It found that Goal 1 (access) and Goal 2 (equity) were successful, but Goal 3 (quality), efficiency, and relevance must be seriously developed.Summary of comments and suggestions for education policy from the seminar about education trends to develop the country in 2018. The seminar runs through a focus group with three levels of experts: policymakers from the central, regional, and schools, including the suggestions from experts and participants who join the seminar that can be synthesized through the urgent policy to promote education management in Thailand.